Blood vessel repair and regeneration in the ischaemic heart. Issue 1 (3rd February 2014) - Zhang, Huajun; van Olden, Casper; Sweeney, Dominic; Martin-Rendon, Enca
Abstract : The term 'therapeutic angiogenesis' originated almost two decades ago, following evidence that factors that promote blood vessel formation could be delivered to ischaemic tissues and restore blood flow. Following this proof-of-principle, safety and efficacy of the best-studied angiogenic factors (eg, vascular endothelial growth factor) were demonstrated in early clinical studies. Promising results led to the development of larger controlled trials that, unfortunately, have failed to satisfy the initial expectations of therapeutic angiogenesis for ischaemic heart disease. As the quest to delay the progression to heart failure secondary to ischaemic heart disease continues, alternative therapies have emerged as potential novel treatments to improve myocardial reperfusion and long-term heart function. The disappointing results of the clinical studies using angiogenic factors were followed by mixed results from the cell therapy trials. This review reflects the current angiogenic strategies for the ischaemic heart, their limitations and discusses future perspectives in the light of recent scientific and clinical evidence. It is proposed that combination therapies may be a new direction to advance therapeutic repair and regeneration of blood vessels in the ischaemic heart.